2017
DOI: 10.5586/asbp.3522
|View full text |Cite
|
Sign up to set email alerts
|

Folk food and medicinal botanical knowledge among the last remaining Yörüks of the Balkans

Abstract: The present study examines the current lifestyle of the last remaining Balkan Yörüks, a small and isolated group found within the Republic of Macedonia, and the modern representatives of an important portion of the Balkan nomads. The aim of this study was to document knowledge concerning local wild food plants and wild and cultivated medicinal plants, and to compare the Yörük ethnobotany with that of similar, more or less isolated ethnic groups occurring in the Balkan region (Macedonia, Bulgaria, Albania, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 35 publications
0
9
0
4
Order By: Relevance
“…Overall the research region showed a lower species number in comparison to a wide variety of studies published from other parts of Europe. The number of food species was low in comparison to other areas in the wider Mediterranean and Caucasus (Carvalho 2016;Dolina et al 2017;Hajdari et al 2018;Kasper-Pakosz et al 2016;Korkmaz et al 2016;Mattalia et al 2020;Melián et al 2017;Mustafa et al 2020;Nedelcheva et al 2017;Oztürk et al 2018;Polat et al 2017;Pawera et al 2017;Pieroni and Cattero 2018;Pieroni andSõukand 2017, 2019;Pieroni 2017;Pieroni et al , 2020Savo et al 2019;Sõukand et al 2017Sõukand et al , 2019Sõukand et al , 2020Yeşil et al 2019), and the number of medicinal species also was lower than in comparative studies (Pieroni and Sõukand 2017;Nedelcheva et al 2017;Melián et al 2017;Sõukand et al-2017;Carvalho 2016;Polat et al 2017;Kasper-Pakosz et al 2016;Korkmaz et al 2016a;Dolina et al 2017, Korkmaz et al 2016bHajdari et al 2018;Oztürk et al 2018;Pawera et al 2017;Pieroni 2017;. The low variety of fungal species used as food was astonishing, especially when compared to other adjacent areas in Georgia, e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Overall the research region showed a lower species number in comparison to a wide variety of studies published from other parts of Europe. The number of food species was low in comparison to other areas in the wider Mediterranean and Caucasus (Carvalho 2016;Dolina et al 2017;Hajdari et al 2018;Kasper-Pakosz et al 2016;Korkmaz et al 2016;Mattalia et al 2020;Melián et al 2017;Mustafa et al 2020;Nedelcheva et al 2017;Oztürk et al 2018;Polat et al 2017;Pawera et al 2017;Pieroni and Cattero 2018;Pieroni andSõukand 2017, 2019;Pieroni 2017;Pieroni et al , 2020Savo et al 2019;Sõukand et al 2017Sõukand et al , 2019Sõukand et al , 2020Yeşil et al 2019), and the number of medicinal species also was lower than in comparative studies (Pieroni and Sõukand 2017;Nedelcheva et al 2017;Melián et al 2017;Sõukand et al-2017;Carvalho 2016;Polat et al 2017;Kasper-Pakosz et al 2016;Korkmaz et al 2016a;Dolina et al 2017, Korkmaz et al 2016bHajdari et al 2018;Oztürk et al 2018;Pawera et al 2017;Pieroni 2017;. The low variety of fungal species used as food was astonishing, especially when compared to other adjacent areas in Georgia, e.g.…”
Section: Discussionmentioning
confidence: 96%
“…It is claimed by some sources that certain food plants identified by us for the area are also used in other regions of Europe (Benítez et al, 2017;Biscotti & Pieroni, 2015;Dénes et al, 2012;Dolina & Łuczaj, 2014;Dolina et al, 2016;Łuczaj et al, 2013Nedelcheva et al, 2017). Species shown by these studies to be consumed cooked or as a salad include the following; Amaranthus sp.…”
Section: Discussionmentioning
confidence: 99%
“…(Dolina & Łuczaj, 2014;Nedelcheva et al, 2017), A. acutifolius (Biscotti & Pieroni, 2015;Dolina et al, 2016;Łuczaj et al, 2013), C. album (Dolina et al, 2016;Łuczaj et al, 2013, M. sylvestris (Nedelcheva et al, 2017), P. rhoeas (Benítez et al, 2017;Biscotti & Pieroni, 2015;Dénes et al, 2012;Dolina & Łuczaj, 2014;Łuczaj et al, 2013), P. oleracea (Biscotti & Pieroni, 2015;Dénes et al, 2012;Dolina et al, 2016), Urtica sp. (Benítez et al, 2017;Biscotti & Pieroni, 2015;Dénes et al, 2012;Dolina & Łuczaj, 2014;Dolina et al, 2016;Łuczaj et al, 2013Nedelcheva et al, 2017), R. acetosella (Dénes et al, 2012;Łuczaj et al, 2015;, R. patientia (Dénes et al, 2012), and R. pulcher (Dolina et al, 2016;Łuczaj et al, 2013, and these results closely resemble our own findings. Species whose fruit are shown to be consumed either raw or as jam by these same studies include: A. unedo).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations